Factors That Influence the Occurring of Rematoid Atritis (RA) in the Elderly in the Region of Puskesmas Raya Pematang Siantar 2021 - Sri Wahyuni Tarigan; Jumadiah Wardati Br Saragih; Meyana Marbun (Institute of Computer Science (IOCS), 2021)
This type of research is cross sectional, this study aims to determine the factors that influence the occurrence of rheumatoid arthritis in the elderly at Pematangsiantar Public Health Center. The subjects of this study were the elderly with a sample of 99 respondents. Data collection tools are questionnaires to answer questions and observation sheets. Rheumatoid arthritis is a disorder in the form of stiffness, swelling, pain and redness in the joints and surrounding tissues. Joint sufferers around the world have reached the number, especially in Indonesia, rheumatoid arthritis reaches 23.6% to 31.3%. This figure shows that the incidence of rheumatoid arthritis is high. There are several factors that influence the occurrence of rheumatoid arthritis in the elderly, namely, genetics, obesity, food and activity/work. This genetic factor influences the occurrence of rheumatoid arthritis in the elderly at Pematangsiantar Public Health Center. The highest frequency which has the highest genetic factor is 12 respondents (12.1%) and the lowest frequency is 87 respondents (87.9%). Obesity factors affect the occurrence of rheumatoid arthritis in the elderly at Pematangsiantar Public Health Center 29 respondents (29%) and the lowest is 70 respondents (70.0%) but affects the incidence of rheumatic arthritis in the elderly. Food factors that influence the occurrence of rheumatoid arthritis have the highest frequency with 86 respondents (86.3%) and the lowest frequency is 13 respondents (13.1%). Activity/occupation factors influence the occurrence of rheumatoid arthritis in the elderly with the highest frequency 76 respondents (76.8%) and the lowest 23 respondents (23 respondents)